2021
DOI: 10.1134/s0036024421030250
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Measurements of Hydrocarbons in Zeolites with Pulse-Field Gradient Nuclear Magnetic Resonance Spectroscopy

Abstract: Pulse field gradient NMR technique was used to determine self-diffusivity of heptane and pentadecane at room temperature for microporous catalysts, used both as powders and shaped with a binder extrudates. The results showed that diffusivities increased with increasing specific surface area, micro-and mesopore volume of the studied catalysts. The presence of Bindzil binder together with H-Beta-25 decreased hydrocarbon diffusivities. Self-diffusivities of heptane and pentadecane were smaller for extrudates than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 31 publications
5
12
0
Order By: Relevance
“…Although it has been observed that diffusivity apparently increases with the Lewis, Brønsted, and overall acidity of the powder catalyst, it can only be a reflection of the textural properties, which, like acidity, varied with the amount of a binder ( Table 1 ). This is in line with the previous observations 7,39 suggesting that strong interactions of acidic zeolites with the hydrocarbons can lead to lower diffusivities, 38 and, on the contrary, that heptane diffusivity increased with the increasing Lewis acidity. 7 No correlation with Lewis or Brønsted acidity was observed for pentadecane diffusion.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Although it has been observed that diffusivity apparently increases with the Lewis, Brønsted, and overall acidity of the powder catalyst, it can only be a reflection of the textural properties, which, like acidity, varied with the amount of a binder ( Table 1 ). This is in line with the previous observations 7,39 suggesting that strong interactions of acidic zeolites with the hydrocarbons can lead to lower diffusivities, 38 and, on the contrary, that heptane diffusivity increased with the increasing Lewis acidity. 7 No correlation with Lewis or Brønsted acidity was observed for pentadecane diffusion.…”
Section: Resultssupporting
confidence: 93%
“…This is in line with the previous observations 7,39 suggesting that strong interactions of acidic zeolites with the hydrocarbons can lead to lower diffusivities, 38 and, on the contrary, that heptane diffusivity increased with the increasing Lewis acidity. 7 No correlation with Lewis or Brønsted acidity was observed for pentadecane diffusion. 7 …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations